The influence of the number of players on workload during small-sided games among elite futsal players - Hulka, K.; Weisser, R. (Montenegrin Journal of Sports Science and Medicine, 2017)
Small-sided games are a specific form of training in which exercise intensity can be manipulated mainly by modifying external factors. The aim of this study was to determine the influence of a number of players during small sided futsal games on metabolic responses and distance covered at elite senior futsal players. Fifteen top level Czech futsal players (males, aged 26.81±5.30; body height = 176.10±4.34 cm; body weight = 71.31±5.30 kg, and peak heart rate=191.23±5.4 beats•min-1) participated in the study. Heart rate, blood lactate concentrations, distance covered, and rate of perceived exertion were monitored during small-sided futsal games. We found significant differences between blood lactate concentration values and perceived exertion; it was significantly higher during 3vs3 and 4vs4 small-sided games than during 6vs6 games. When we compared the distance covered by players, we found significantly higher distance covered during 4vs4 than in 6vs6 games. The results of this study demonstrated that the small-sided games 3vs3 and 4vs4 were valuable tools to develop specific futsal fitness. As the most intensive, the 4-a-side game was found.